Analysis of Circulation and Parking as Elements Shaping Marisa City Based on Geographic Information Systems to Support Sustainable Infrastructure - Umar, Indriani; Rudi (Cattleya Darmaya Fortuna, 2026)
Urban circulation and parking systems are essential elements shaping city structure and influencing the sustainability of urban infrastructure. This study aims to analyze circulation patterns and parking distribution in Marisa City using a Geographic Information Systems (GIS) approach to support sustainable infrastructure planning. A quantitative spatial analysis was applied through network analysis, buffer analysis, and overlay analysis to evaluate road connectivity, accessibility, parking service coverage, and the interaction between traffic intensity and parking locations. The results indicate that circulation in Marisa City is dominated by collector and local roads with moderate connectivity, leading to traffic concentration in commercial areas. Parking analysis reveals a heavy reliance on on-street parking, resulting in reduced road capacity and circulation inefficiencies. Spatial mismatch between parking demand and supply is evident, particularly in commercial zones. The findings highlight that poorly integrated circulation and parking systems negatively affect accessibility, land use efficiency, and environmental sustainability. This study emphasizes the importance of GIS-based planning as a decision-support tool for optimizing circulation and parking management to promote sustainable urban infrastructure development in Marisa City.